Making the most of platforms: a policy and research agenda - Coyle, Diane (Toulouse, 2016)
"Digital platforms are proliferating in many countries and many sectors of the economy. Platforms create immense value, for their customers and also for their suppliers. Yet all too often they are seen only through the lens of the ‘disruption’ of incumbents, resulting in a narrow debate about whether platforms should be more heavily regulated. Yet the right questions are: what policy framework will ensure the immense benefits are encouraged and widely shared; what will help create new platforms, and sustain healthy competition and innovation; and how can unwelcome aspects of platform behaviour be avoided? This paper gives a broad overview of theory and evidence to date on digital platforms and aims to set out the issues that remain to be addressed by researchers, policymakers, and the platform businesses themselves. The distinctive economic characteristics of platforms, their global scope and their rapid evolution make for a rapidly-changing landscape in which traditional policy tools and business strategies do not apply, and there are many questions to be answered."